2022
DOI: 10.1097/aud.0000000000001227
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Hearing Difficulties Are Associated With Lower Inhibitory Control

Abstract: Objective: Evidence suggests that hearing loss increases the risk of cognitive impairment. However, the relationship between hearing loss and cognition can vary considerably across studies, which may be partially explained by demographic and health factors that are not systematically accounted for in statistical models.Design: Middle-aged to older adult participants (N = 149) completed a web-based assessment that included speech-in-noise (SiN) and self-report measures of hearing, as well as auditory and visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Some people with specific characteristics are more likely to have hearing loss, or report hearing loss than others. For example, in a recent study conducted by our group, we found significant differences in speech-in-noise ability between males and females, with males showing a higher loss than females [ 23 ]. We also observed that the likelihood of reporting hearing loss is affected by age, depression, anxiety, age, and self-reported health status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some people with specific characteristics are more likely to have hearing loss, or report hearing loss than others. For example, in a recent study conducted by our group, we found significant differences in speech-in-noise ability between males and females, with males showing a higher loss than females [ 23 ]. We also observed that the likelihood of reporting hearing loss is affected by age, depression, anxiety, age, and self-reported health status.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of predictors was based on the hearing aid literature [ 24 26 ], which shows that these variables are associated with hearing amplification benefits. We additionally included the self-reported measure of hearing because it has been shown that objective and subjective measures of hearing do not correlate strongly and may reveal different aspects of hearing ability [e.g., 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The two other studies, however, reported no significant relationships (Völter et al, 2018(Völter et al, , 2020. Correlations with SSQ and cognitive ability in hearing aid users (not CI users) revealed that lower SSQ outcomes correlated with lower inhibitory control (Perron et al, 2022) and slower processing speed (Ng et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…Another study suggests auditory streaming task performance and reaction times are sensitive to both cognitive and auditory abilities [37]. Three articles [38][39][40] indicated WMC and IC (Inhibitory Control) may be causative factors for SIN performance and may be considered clinically. Lentz, Humes and Kidd (2022) [41] indicate that performance for psychoacoustic tasks, hearing (50% of tasks) and cognition (75% of tasks) are important factors.…”
Section: Speech-in-noise (Sin) Cognitive Variablesmentioning
confidence: 99%